Pembuatan Manipulasi Tekstil Dengan Teknik Fabric Slashing Pada Ready To Wear - Ariyana Damayanti; Utari Dwi Harianti (Garina, 2022)
The fabric slashing technique is the appearance of a clothing that requires modifications to beautify the clothing. The way to beautify a garment is to be creative by using the fabric slashing technique which can make the garment more attractive. The purpose of this technique is to explain about the fabric slashing technique process along with making clothes that will be applied to ready to wear. Descriptive method is done by looking for information related to the technique. The fabric slashing technique uses a piece of cloth that is cut according to a pattern. This technique will be a research on how to do slashing techniques on ready to wear which will produce new motifs and textures on the surface of the fabric. This research produces new motifs and textures on the surface of the fabric that will look oozing at the edges. This research uses vertical and horizontal line motifs on the fabric surface. The slashing technique can be further expanded on the design with various variations such as changing the shape, size and color. The types of materials used can vary to see the results of the materials obtained are right or not.